Cardiomyocyte Expression of ZO-1 Is Essential for Normal Atrioventricular Conduction but Does Not Alter Ventricular Function. Issue 2 (3rd July 2020) - Zhang, Jianlin; Vincent, Kevin P.; Peter, Angela K.; Klos, Matthew; Cheng, Hongqiang; Huang, Selina M.; Towne, Jordan K.; Ferng, Debbie; Gu, Yusu; Dalton, Nancy D.; Chan, Yunghang; Li, Ruixia; et al.
Abstract : Rationale: ZO-1 (Zonula occludens-1), a plasma membrane-associated scaffolding protein regulates signal transduction, transcription, and cellular communication. Global deletion of ZO-1 in the mouse is lethal by embryonic day 11.5. The function of ZO-1 in cardiac myocytes (CM) is largely unknown. Objective: To determine the function of CM ZO-1 in the intact heart, given its binding to other CM proteins that have been shown instrumental in normal cardiac conduction and function. Methods and Results: We generated ZO-1 CM-specific knockout (KO) mice using α-Myosin Heavy Chain-nuclear Cre (ZO-1cKO) and investigated physiological and electrophysiological function by echocardiography, surface ECG and conscious telemetry, intracardiac electrograms and pacing, and optical mapping studies. ZO-1cKO mice were viable, had normal Mendelian ratios, and had a normal lifespan. Ventricular morphometry and function were not significantly different between the ZO-1cKO versus control (CTL) mice, basally in young or aged mice, or even when hearts were subjected to hemodynamic loading. Atrial mass was increased in ZO-1cKO. Electrophysiological and optical mapping studies indicated high-grade atrioventricular (A-V) block in ZO-1cKO comparing to CTL hearts. While ZO-1-associated proteins such as vinculin, connexin 43, N-cadherin, and α-catenin showed no significant change with the loss of ZO-1, Connexin-45 and Coxsackie-adenovirus (CAR) proteins were reduced in atria of ZO-1cKO. Further, with loss of ZO-1, ZO-2 protein was increased significantly in ventricular CM in a presumed compensatory manner but was still not detected in the AV nodal myocytes. Importantly, the expression of the sodium channel protein NaV1.5 was altered in AV nodal cells of the ZO-1cKO versus CTL. Conclusions: ZO-1 protein has a unique physiological role in cardiac nodal tissue. This is in alignment with its known interaction with CAR and Cx45, and a new function in regulating the expression of NaV1.5 in AV node. Uniquely, ZO-1 is dispensable for function of the working myocardium. Abstract : Supplemental Digital Content is available in the text.